FAKTOR KARAKTERISTIK YANG BERHUBUNGAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN GANGGUAN JIWA - Vivi Yuderna; Triyana Harlia Putri (STIKES Syedza Saintika Padang, 2024)
Medication adherence is a medication given to patients with mental disorders (ODGJ). Patients who are not compliant in their treatment will have an impact on relapse. One of the factors that can determine patient compliance in undergoing treatment is the characteristic factor. Therefore, this study aims to identify factors related to the presence of patients with mental disorders. This type of research is quantitative with a cross-sectional approach. The population of this study was 48 people with mental disorders (ODGJ) who visited the Sungai Sariak Health Center, West Sumatra, so that sampling used the total sampling technique. The instruments used in this study used a demographic questionnaire and the Medication Adherence Reating Scale (MARS) for psychosis. Bivariate analysis using the chi-square test. The proportion of respondents who were not compliant in taking medication was higher in young adult respondents (62.1%), most respondents were compliant (54.2%) although there was no significant difference with patients who were not compliant in taking medication (45.8%), young adults had a fairly high frequency (62.1%) who were not compliant in taking medication, followed by men (53.1%), low education (57.1%), low economic status (68.4%) and unmarried (81.8%) were also reported to be non-compliant in taking medication. The chi-square results obtained by all individual factors fell asleep on the fulfillment of taking medication, namely p <0.05, but not with the gender factor. Significant characteristic factors from marriage to marriage were age, education level, economic level and marital status except gender was not related to marriage.Keywords : Compliance; ODGJ; Relapse